Case report: Epilepsy during the use of recombinant human growth hormone: a report on two cases and a literature review - Zhou, Yuan; Jia, Ruofan; Xu, Zhuangjian; Ma, Yaping (Frontiers in Pharmacology, 2024)
Background Epilepsy during recombinant human growth hormone (rhGH) therapy is rare in children. The potential association between rhGH treatment and epilepsy remains unclear. Methods We retrospectively analyzed the clinical data of two Chinese boys who experienced epilepsy during the use of rhGH and reviewed the relevant literature. Results: Case 1, an 8-year and 2-month-old boy, was diagnosed with short stature, malnutrition, and congenital hypothyroidism. He was on levothyroxine sodium tablets for a long time. Recurrent febrile convulsions were present at 6–7 years. Electroencephalogram and magnetic resonance imaging (MRI) showed no abnormality, and no treatment was given. He was diagnosed with complex febrile convulsions. The boy started rhGH treatment (approximately 0.15 IU/kg/day, sc, qd) at 8 years and 4 months. Epilepsy occurred three times during the 6 months of rhGH treatment. Electroencephalography confirmed a definitive diagnosis of epilepsy. Then, he discontinued rhGH treatment at 8 years and 11 months and started taking levetiracetam (0.25 g, po, bid) for antiepileptic therapy. Epilepsy was well-controlled 4 months later. He continued rhGH treatment at 10 years and 3 months and has been on rhGH treatment until now, with no recurrence of epilepsy. He has been taking levetiracetam to date. Case 2, a 9-year and 1-month-old boy, was diagnosed with central precocious puberty, predicted short final height, and overweight. He started treatment with triptorelin (3.75 mg, im, q4w) and rhGH (approximately 0.15 IU/kg/day, sc, qd) at 9 years and 3 months. He tended to fall repeatedly when he was approximately 10 years old. Electroencephalography showed a few medium- to high-amplitude sharp waves and sporadic sharp slow waves in the left middle temporal region, sometimes involving the left posterior temporal region. He was diagnosed with epilepsy. Triptorelin discontinuance provided no symptom relief, which worsened further. Subsequently, he withdrew from rhGH treatment, and the symptoms occurred occasionally within a week and stopped after 15 days. The electroencephalogram returned to normal. No further seizures occurred during follow-up to date. Conclusion During the use of rhGH in short-stature children with complex febrile convulsions or underlying lesions related to neurological impairment or those being treated with antiepileptic drugs, epilepsy may be induced.